2011
DOI: 10.1097/crd.0b013e31821ddcf4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonsteroidal Anti-Inflammatory Drugs on Blood Pressure in Hypertensive Patients

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are ubiquitous medications used by a wide range of people from otherwise healthy normotensive patients to hypertensive patients with many significant comorbidities. Through a variety of mechanisms related to prostaglandin inhibition, including sodium retention and vasoconstriction, these agents may increase blood pressure. This leads to potentially detrimental effects. A review of the current literature regarding this topic yielded 2 meta-analyses and 10 randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 44 publications
0
42
1
2
Order By: Relevance
“…Patients with HT showed variable increases with NSAID treatment, i.e. up to +14.3 mm Hg for systolic BP and +2.3 mm Hg for diastolic BP [46]. However, multivariate analysis revealed no significant correlation between NSAID usage and HT in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Patients with HT showed variable increases with NSAID treatment, i.e. up to +14.3 mm Hg for systolic BP and +2.3 mm Hg for diastolic BP [46]. However, multivariate analysis revealed no significant correlation between NSAID usage and HT in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…First, previous studies have documented that NSAIDs, to some extent, have an impact on vasoconstriction and sodium excretion, which can increase blood pressure and subsequently lead to an increased risk of cerebrovascular events. [21][22][23] Second, NSAIDs inhibit the activity of the COX isozymes (COX-1 and COX-2) and block prostanoid biosynthesis. As a result, NSAIDs decrease total renal perfusion and lead to redistribution of renal blood flow, particularly in vulnerable populations, which may cause medullary ischemia and even acute renal failure.…”
Section: April 2015mentioning
confidence: 99%
“…Several studies and meta-analysis found that NSAIDs can increase blood pressure [69]. In normotensive patients, NSAIDs increases mean blood pressure by 5 mm Hg [52], particularly in patients with pre-existing hypertension: increase up to 14.3 mm Hg for systolic pressure and 2.3 mm Hg for diastolic blood pressure [69].…”
Section: Hypertensionmentioning
confidence: 99%